TARI DOLALAK SEBAGAI IDENTITAS MASYARAKAT KABUPATEN PURWOREJO - Sentri Captian Ningsih (Saraswati)
This journal will discuss about Dolalak Dance as a symbol of identity, in several simultaneous dance carries information channels of a community has a great potential to communicate something about themselves, especially in different situations where people interaction. That complex characteristics are used to mark or identity that emerge in the community is a style. Forcely composed of symbols, shapes, and orientations underlying value. Shapes and symbols openly put clothes, language, music dance, type house, and religion are supported by such values ​​of friendship, and education. In other words, a dance that grows and develops in a society has the style and context of each accordance with occurs in society. To the analysis that will be discuss namely the elements of motion, makeup and fashion, as well as the musical accompaniment that included a poem with a pattern as a commuting Purworejo to bring up the context of their communities.The context relate with the Dolalak dance as a behavior of Purworejo populations is an expression of live society as a society Purworejo.   Keywords: dance, Dolalak, Purworejo.